Dendritic cells in melanoma therapy - Markowicz, Sergiusz (Contemporary Oncology/Współczesna Onkologia, 2003)
Dendritic cells (DC) are the most efficient stimulators of T lymphocyte response among professional antigen presenting cells (APC), and the only APC capable to prime naive T lymphocytes with the antigen. A response to weakly immunogenic and tolerogenic tumor antigens can be achieved with the use of DC as APC. DC pulsed with oligopeptides derived from melanoma antigens induced in vitro antigen-specific cytotoxic T lymphocytes capable to lyse melanoma cells. Primary in vitro immunization with peptide-pulsed DC was used to select melanoma-specific cytotoxic T-lymphocyte epitopes for melanoma immunotherapy. Objective clinical responses were observed in a substantial part of melanoma patients vaccinated with DC pulsed ex vivo with tumor antigens. DC-based vaccinations caused regression of metastases in various organs, and elicited melanoma-specific cytotoxic T lymphocytes and delayed-type hypersensitivity to peptide-pulsed DC. The vaccinations were well tolerated and safe. DC were used to generate specific cytotoxic T CD8+ lymphocytes from metastatic melanoma patients for adoptive therapy. Adoptively transferred T cell clones preferentially localized to tumor sites and mediated antigen-specific immune response. Antigen-positive tumor cells were eliminated and regression of individual metastases was observed. Appropriate antigen selection for immunization, optimizing of methods of DC isolation, culture and administration, and improvement of strategy of vaccine timing and dosage may increase the effectiveness of DC-based vaccination in cancer.